Investigation of the organic solar cell characteristics for indoor LED light applications. (25th June 2015) - Mori, Shigehiko; Gotanda, Takeshi; Nakano, Yoshihiko; Saito, Mitsunaga; Todori, Kenji; Hosoya, Masahiro
Abstract: We report an experimental study on the current–voltage characteristics of organic solar cells (OSCs) under indoor light illumination. A daylight color light-emitting diode (LED) was used as the indoor light source. We investigated the short circuit current density, open circuit voltage, and fill factor of the OSC under LED irradiation and compared them with those for a crystal silicon solar cell (c-Si-SC), which occupy a large part of the solar cell market. We found that compared with the c-Si-SC, the OSC had higher power conversion efficiency (PCE). We also derived the maximum feasible PCE of an OSC for indoor applications and calculated that a PCE value of 21.3% could be obtained under daylight color LED illumination at approximately 200 lx. From the results of the calculation, it became apparent that the open circuit voltage plays an important role in achieving a high PCE from OSCs, indicating they are promising as electrical energy harvesting module for indoor applications.